Coastal Management in Australia - Harvey, Nick (University of Adelaide Press, 2010)
The coast is one of our most valuable assets but how is it being treated and what is being done to look after it? Coastal Management in Australia is the first book to provide a comprehensive overview of this important subject. Interesting case studies are used to illustrate human impact on coastal processes as well as demonstrating the global significance of the coast and the international imperative to manage it properly. Coastal Management in Australia introduces the background to the various coastal management systems operating in Australia and illustrates these with 'real world' examples from the different states and territories. Since this book was first published yet another parliamentary inquiry has been added to some 30 years of national inquiries into coastal management, with further calls for national co-ordination. In addition, the Australian government has focused attention on the potential risks of climate change for the Australian coast. Both authors have national and international coastal expertise; significant academic teaching experience in coastal processes and coastal management; coastal planning and policy skills; and have extensive government expertise in coastal management.